"THE CONCEPT OF HOMELAND IN B. ISKAKOV’S POETIC PICTURE OF THE WORLD" - M. Kildiroglu; K. M. Shakirova; A. Ye. Amangaliyeva (Toraighyrov University, 2023)
"The article is devoted to the study of the concept «Homeland» in the poetic picture of the world of the Kazakh poet B. Iskakov. The material of the study is the poetic texts of B. Iskakov, which are considered as a form of linguistic representation of the individual author’s picture of the world. The relevance of the research is stipulated by the fact that the work is carried out in the framework of modern linguistic trends (cognitive linguistics and cognitive poetics) and contributes to the solution of such an important problem of modern gnoseolinguistics as revealing the specificity of national conceptosphere and its constituent concepts. The article presents the results of the linguistic and cognitive analysis, where the national and cultural essence and mentality of the Kazakh people, the content of cognitive signs, the deep meaning of native land in the poet’s understanding are revealed through the concept «Homeland» in the language of the poet. Several interrelated conceptual fields have been identified in the structure of the «Homeland» concept («golden cradle», «immediate family», «native land», «native nature», «native home», «sacred place»), as part of conceptual fields – cognemas («nostalgia«, «beauty», «mother», «happyness», «sunrise»,) are revealed. This shows the versatility and complexity of this mental entity and allows it to be characterized as a concept. Particular attention is paid to the analysis of such specific means of verbalization of this concept in B. Iskakov’s poetic picture of the world as toponyms, the method of staggered extension of the image, compressed form of expression, bright metaphors, comparisons and epithets. Keywords: concept, conceptual model, cognema, author’s picture of the world, cognitive theory, cognitive character, worldview. "